PENGARUH PROBING PROMPTING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA MATERI SISTEM KOORDINASI KELAS XI SMA NEGERI 5 METRO - Meiliza Tri Santika; Widya Sartika Sulistiani; Triana Asih (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
The aim of this research is to determine the effect of the Discovery Learning model on the critical thinking skills of students of grade XI SMA Negeri 5 Metro. This type of research is quasi-experimental research that is quasi experimental research (quasi experimental research). The research design used in this research is Post-test Only Control Design with Non-equivalent Control Group Design. The sampling technique used in this research is Cluster Random Sampling technique because the population consists of individual groups (Clusters). The population used is all students of class XI IPA SMA Negeri 5 Metro Lesson Year 2019/2020 includes 4 classes consisting of 128 students. The sample used consisted of two classes. This research uses two classes: control class applied by conventional learning model and experiment class applied by model of Probing Prompting. The biological material studied using the model of Probing Prompting is Sistem Koordinasi in the class XI IPA of odd semester. This research was conducted at SMA Negeri 5 Metro located at JalanWolter Monginsidi Metro pusat. Data analysis of research result using parametric test of t-test.Based on the results of research, about the influence of the Probing Prompting model on students 'critical thinking ability, it can be concluded that the Probing Prompting model has an effect on the students' critical thinking ability as evidenced by the result of the relevant hypothesis test that is t-test that thit (89,9) is bigger than tdaf (2,39) in level of significance 0,01, so that model of Probing Prompting influence to critical thinking ability of student of class XI SMA Negeri 5 Metro.